Penerapan Metode Pembelajaran Peer Teaching untuk Meningkatkan Keaktifan dan Hasil Belajar Akuntansi Siswa - Kusumawardhana, Ap Massri M; Sahria, Yoga; Santosa, Budi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to improve the activeness and learning outcomes of accounting students in grade XI AKL 3 SMK Negeri 1 Kaligondang through the application of  the Peer Teaching (Peer Tutor) learning method. The research method used is Classroom Action Research (PTK) which is carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The results of the study showed an increase in student learning activity from cycle I to cycle II with an average increase of 9.76%. In this regard, student learning outcomes also increased with classical completeness reaching 86.84% in cycle II. The implementation of the Peer Teaching method has proven effective in improving students' activeness and accounting learning outcomes. This method allows students to learn collaboratively and help each other, thereby increasing their participation and understanding of the material. This study provides a positive contribution to the development of learning methods in schools, especially in accounting subjects.